2016
DOI: 10.1371/journal.pone.0153158
|View full text |Cite
|
Sign up to set email alerts
|

Seamless Insert-Plasmid Assembly at High Efficiency and Low Cost

Abstract: Seamless cloning methods, such as co-transformation cloning, sequence- and ligation-independent cloning (SLIC) or the Gibson assembly, are essential tools for the precise construction of plasmids. The efficiency of co-transformation cloning is however low and the Gibson assembly reagents are expensive. With the aim to improve the robustness of seamless cloning experiments while keeping costs low, we examined the importance of complementary single-stranded DNA ends for co-transformation cloning and the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 30 publications
1
36
1
Order By: Relevance
“…S4) to fulfill seamless assembly of DNA fragment(s) derived from Cas9 RNP cleavage. In accordance with previous reports [43][44][45] , we found that the efficiency of EI method drops sharply when the number of gene fragments is over three. So, the T5-assisted cloning is preferable when assembling three or more gene fragments.…”
Section: Single Cas9 Rnp-based Seamless Dna Assemblysupporting
confidence: 93%
See 1 more Smart Citation
“…S4) to fulfill seamless assembly of DNA fragment(s) derived from Cas9 RNP cleavage. In accordance with previous reports [43][44][45] , we found that the efficiency of EI method drops sharply when the number of gene fragments is over three. So, the T5-assisted cloning is preferable when assembling three or more gene fragments.…”
Section: Single Cas9 Rnp-based Seamless Dna Assemblysupporting
confidence: 93%
“…Though GA is fast and versatile, it is very expensive because it requires three enzymes including T5 exonuclease, Phusion DNA polymerase and Taq DNA ligase. Meanwhile, enzyme-independent cloning (EI) methods 43,44 have been developed capable of assembling DNA fragments without any enzyme at low cost. In a typical EI cloning (Fig.…”
Section: Single Cas9 Rnp-based Seamless Dna Assemblymentioning
confidence: 99%
“…Therefore, any improvement in protein yield and purity makes the research more cost-effective and supports approaches to investigate protein function, applying for example alanine scan methodology [41, 42]. The availability of restriction enzyme free cloning strategies, such as the seamless cloning technique [43], allows a broad application of our expression cassette using the strong paf promoter/terminator. Penicillium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the Hot Fusion method 15, 23 can be used for assembling two fragments instead of the Gibson reaction, which further reduces the cost of mutagenesis by omitting a DNA ligase.…”
Section: Resultsmentioning
confidence: 99%